1997
DOI: 10.1021/jp962303e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Enthalpies of Formation of NHmCln:  Neutral Molecules, Cations, and Anions

Abstract: Ab initio molecular orbital calculations are reported for all neutrals, anions, and cations of the formula NH m (m = 1−3) and for their chlorinated analogues NH m Cl n (m + n = 1, 2, or 3). Structures were optimized using gradient techniques at HF/6-31++G(d,p) and at MP2(full)/6-311++G(d,p). Single-point calculations are reported at MP4SDTQ(fc)/6-311++G(2df,p) and at QCISD(T)(full)/6-311++G(2df,p) levels using geometries optimized at MP2. Standard enthalpies of formation have been calculated at MP4SDTQ(fc)/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
24
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 77 publications
8
24
1
Order By: Relevance
“…36 However, these available computed AIE and/or EA values of PnCl 2 were obtained at different levels of theory and also at significantly lower levels than the best estimates for AsCl 2 benchmarked in this study. To compare computed AIE and EA values for the PnCl 2 (Pn 5 N, P, As, and Sb) series on the same footing, we have performed G4 calculations 42 on NCl 2 , PCl 2 , and AsCl 2 and their cations and anions, using GAUSSIAN09, 43 and further RCCSD(T) calculations (see footnotes e, f, and g of Table 6 for details) on SbCl 2 and its cation and anion using …”
Section: Discussioncontrasting
confidence: 54%
“…36 However, these available computed AIE and/or EA values of PnCl 2 were obtained at different levels of theory and also at significantly lower levels than the best estimates for AsCl 2 benchmarked in this study. To compare computed AIE and EA values for the PnCl 2 (Pn 5 N, P, As, and Sb) series on the same footing, we have performed G4 calculations 42 on NCl 2 , PCl 2 , and AsCl 2 and their cations and anions, using GAUSSIAN09, 43 and further RCCSD(T) calculations (see footnotes e, f, and g of Table 6 for details) on SbCl 2 and its cation and anion using …”
Section: Discussioncontrasting
confidence: 54%
“…For HNCl, there is no experimental determination available. Milburn et al 16 have reported singlepoint MP4 and QCISD(T) calculations with MP2 optimized geometry for all NH m Cl n species with the same large basis set, 6-311++G**. Their results are in very good agreement with the G2 values reported here for HNCl 2 , HNCl, NCl 2 , NH, and …”
Section: Iii2b Hnclsupporting
confidence: 82%
“…For HNF 2 and HNCl 2 , our results exactly agree with the ab initio results previously reported at the same levels. 16,17 For HNF 2 , the N-H distances calculated by MP2 and DFT methods are within 0.003 Å from the experimental value, 28 accurately determined from its rotational spectrum(1.026 Å). The same is true for the N-F distance calculated by DFT method but the deviation is 0.009 Å for the MP2/6-311++G** level calculation.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Up to now, quantum-chemical calculations were performed for a wide variety of nitrenium ions: NH 2 + [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], MeNH + [22,24,25,30,36,41], Me 2 N + [22,24,25,30,41], MeAcN + [22], (CH 2 ) 2 N + [42], (CH 2 ) 4 N + , (CH 2 ) 5 N + [22,24,25], (XCH=CH)MeN + (X = H, Cl) [25], (CH) 2 N + , CHN 2 + [43], (CH) 6 N + [44], XN 3 + (X = O, S, Se, Te) [45], XNH + (X = NH 2 , PH 2 , OR, SH, Cl, F, Br, I, CN, NC 2 ) [23,27,28,32,34,36,40,46], X(CHO)N + [X = N, NH 2 , PH 2 , OR, SH, Ph(CH 2 ) n O] …”
Section: Electronic Structure and Properties Of Nitrenium Ionsmentioning
confidence: 99%